Large momentum transfer Raman atom interferometer without -reversal - Peng,G; Lanigan,B; Shah,R; Lim,J; Kaushik,A; Cotter,J; Hinds,E; Sauer,B (Physical Review Research, 2025)
We present a Raman atom interferometer using large momentum transfer without reversing thedirection of the effective wavevector (k-reversal). More specifically, we use a microwave π/2 pulseto manipulate the spin state of Rb atoms before applying a Raman light π pulse to achieve 4k momentum transfer per Raman light pulse. A microwave π pulse in the middle of the interferometer sequence reverses the spin states, which allows closing of the interferometer arms by the same Raman light π pulses without propagation reversal. We present a proof-of-principle demonstration of a 4klarge-momentum-transfer (LMT) atom interferometer and discuss its scalability. Our results extend the scope of using LMT atom optics.